Influence of benzyl and phenyl substitution in phosphonate-based ionic liquids on cellulose dissolution: Experimental and COSMO-RS insights - Imran Emon; Niwanthi Dissanayake; Carson Smith; Andi Cantu; Zeyad Zeitoun; Shaida Rumi; Rohan S. Dassanayake; Noureddine Abidi; Vidura Thalangamaarachchige (Carbohydrate Polymers, 2026)

Spectrum of DNA Variants Underlying Deafness in an Ecuadorian Cohort - Anghela Reinoso-Castillo; Memoona Ramzan; Andrea Carrera-Gonzalez; Christian Rivas-Iglesias; Stefanny Montufar; Rodrigo Vinueza-Gavilanes; Carson Smith; Arianne Llamos-Paneque; Mustafa Tekin (Biochemical Genetics, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Proposed key characteristics of neurotoxic chemicals - Pamela J. Lein; Aaron B. Bowman; Zhengyu Cao; Monica Carson; Brenda Eskenazi; Ellen Fritsche; G. Jean Harry; Thomas Hartung; Isaac N. Pessah; William Slikker; Lauren Zeise; Martyn T. Smith (NeuroToxicology, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Functional brain network correlates of cardiorespiratory fitness and moderation by depression symptoms - Lauren R. Borrell; Andrew C. Venezia; J. Carson Smith (Brain Structure and Function, 2025)
Cardiorespiratory fitness may protect against or alleviate depression through neuroplastic mechanisms within disrupted brain networks underlying cognitive and affective symptoms. There is a scarcity of research examining the effects of cardiorespiratory fitness on functional brain networks in representative samples spanning adulthood. Further, little is known about the interaction of cardiorespiratory fitness with depression in these networks. To address this problem, this study made use of the NKI-Rockland sample dataset and magnetic resonance imaging to examine whether functional brain network features associated with cardiorespiratory fitness were moderated by depression symptom severity in a community sample of 217 participants (134 females, 83 males) between the ages of 18 and 71 ( M = 43.8 years, SD = 16.2). Cardiorespiratory fitness was positively associated with whole-brain modularity, between-network connectivity of the central executive and salience networks, and within-network connectivity of the default mode, central executive, and salience networks. The association of cardiorespiratory fitness and default mode network connectivity was stronger in the presence of moderate-to-severe depression symptoms. Taken together, these observations lend support to prior work that has demonstrated the associations of cardiorespiratory fitness with reduced concurrent and prospective depression risk and symptom severity. Depression symptoms moderated default mode network connectivity, suggesting that cardiorespiratory fitness may differentially impact neural substrates for those with moderate-to-severe depression symptoms.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Evaluation of later timepoints for fixed-time artificial insemination of beef heifers and cows when using sex-sorted semen - Genevieve M. VanWye; Carson M. Andersen; Emily G. Smith; Zachary L. Erwin; Christine Spinka; Scott E. Poock; Jordan M. Thomas (Theriogenology, 2024)

Associations between PM2.5 and O3 exposures and new onset type 2 diabetes in regional and national samples in the United States - Tara P. McAlexander; Victoria Ryan; Jalal Uddin; Rania Kanchi; Lorna Thorpe; Brian S. Schwartz; April Carson; Deborah B. Rolka; Samrachana Adhikari; Jonathan Pollak; Priscilla Lopez; Megan Smith; et al. (Environmental Research, 2023)

Basal forebrain functional connectivity as a mediator of associations between cardiorespiratory fitness and cognition in healthy older women - Junyeon Won; Laszlo Zaborszky; Jeremy J. Purcell; Sushant M. Ranadive; Rodolphe J. Gentili; J. Carson Smith (Brain Imaging and Behavior, 2023)

Retrospective chart analysis to determine the impact of a patient-facing digital risk stratification tool combined with a clinical screener for hereditary cancer genetic risk assessment triage in a community oncology clinic - Kate P. Shane-Carson; Douglas Smith; Angie Smith; Caroline Seeley (Journal of Community Genetics, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Phase II MS4 challenges: moving toward effective stormwater management for small municipalities - Leslie Rieck; Craig Carson; Robert J. Hawley; Madison Heller; Mike Paul; Mateo Scoggins; Mel Zimmerman; Robert F. Smith (Urban Ecosystems, 2022)
Federal regulations for municipal separate storm sewer systems (MS4s) in the United States have been in place since 1990 as part of the Nation Pollutant Discharge Elimination System (NPDES), aiming to reduce sediment and pollutant loads originating from urban areas. However, small-municipality (Phase II) MS4s frequently grapple with several challenges, resulting in a lack of stakeholder buy-in and actionable stormwater management plans. We identify five common challenges concerning MS4 requirements based on literature review, professional experience, and feedback solicited from stakeholders, municipal managers, and fellow professionals and offer real-world examples of efficient, effective MS4 frameworks and/or solutions. The five challenges are summarized as beliefs that: (1) agricultural land use is the largest pollutant contributor and the root cause of pollution problems; (2) stormwater management only benefits downstream communities; (3) large, expensive projects are required to comply with regulations; (4) maintenance, monitoring, and inspection of best management practices (BMPs) is overwhelmingly complex and expensive; and (5) a lack of direct funding makes complying with regulations an impossible task. These challenges are universal in nature for Phase II MS4 permittees and can create real barriers for effective stormwater management. However, we found many examples of methods or techniques to effectively address these five specific challenges, making them well-suited and important for discussion. BMPs can create tangible improvements for surrounding communities (e.g., reduced streambank erosion and flooding), and improved understanding of the structure and options within the MS4 program will help small municipalities make informed choices about management plans.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The hidden legacy of megafaunal extinction: Loss of functional diversity and resilience over the Late Quaternary at Hall’s Cave - Carson P. Hedberg; S. Kathleen Lyons; Felisa A. Smith (Global Ecology and Biogeography, 2022)
Aim Functional traits mediate the interactions of species among themselves and with their environment, providing a link between diversity and ecosystem function. Crucially, the loss of biodiversity can jeopardize the functionality of ecosystems. Much focus is on predicting the impacts of current and future species loss; however, modern ecosystems have undergone biodiversity decline throughout the Late Quaternary, starting with the Pleistocene megafaunal extinctions. Thus, the fossil record offers the opportunity to investigate the long‐term legacy of biodiversity erosion and how this is affecting modern ecosystems in a cumulative manner. We aimed to investigate changes in functional diversity and redundancy of a local mammal community at Hall’s Cave, a site with a continuous record from 21,000 years ago to the present. Additionally, we included several common introduced species in the modern community to test whether they restore some lost ecological function. Location Central Texas. Time period Late Pleistocene to Present. Major taxa studied Mammals. Methods We used eight functional traits (mass, diet, arboreality, cursoriality, soil disturbance, group size, activity period and migration habit), which, collectively, describe the ecological role of a species and its influence on ecosystem processes, to construct a multidimensional functional space. The functional richness, range and distribution of the Hall’s Cave community and the degree of functional redundancy were characterized statistically over time. Results We found that declines in functional diversity were greater than expected given the decrease in species richness, implying that lost taxa contributed higher than average distinct ecological function. Functional distances between the remaining species increased through time, leading to reduced functional redundancy in younger communities. However, recently introduced taxa increased functional diversity to levels similar to those in the Holocene and partly restored the functional space occupied by Late Pleistocene fauna. Main conclusions Our local‐scale analysis demonstrates how prolonged biodiversity erosion not only leads to functionally depauperate communities, but, crucially, lowers ecological resilience to future disturbance.

Association Between Greater Cerebellar Network Connectivity and Improved Phonemic Fluency Performance After Exercise Training in Older Adults - Junyeon Won; Yasmeen Faroqi-Shah; Daniel D. Callow; Allison Williams; Adewale Awoyemi; Kristy A. Nielson; J. Carson Smith (The Cerebellum, 2021)

Technological advances in maize breeding: past, present and future - Carson Andorf; William D. Beavis; Matthew Hufford; Stephen Smith; Walter P. Suza; Kan Wang; Margaret Woodhouse; Jianming Yu; Thomas Lübberstedt (Theoretical and Applied Genetics, 2019)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)